What is appropriate and relevant assistance after a disaster? Accounting for culture(s) in the response to Typhoon Haiyan/Yolanda. (June 2017) - Field, Jessica
Abstract: Typhoon Haiyan, known locally as Yolanda, was one of the strongest typhoons to hit the Philippines in recent history, killing over 6000 people when it made landfall in November 2013. The international humanitarian response was fast and expansive, with post-response evaluations noting it as largely successful. This study, however, reveals a disconnect between international humanitarian and affected-community understandings of effectiveness, and roots the division in an under-acknowledged difference of cultures between the international humanitarian system and the people receiving assistance. Challenging official humanitarian framings of appropriateness and relevance, this study posits the need for a more localised, contextualised and culturally-sensitive approach to understanding post-disaster needs and vulnerabilities.